Discovering category boundaries: The role of comparison in infants' novel category learning. (31st January 2022) - Sučević, Jelena; Althaus, Nadja; Plunkett, Kim
Abstract: A key question in categorization is how infants extract regularities from the exemplars they encounter. Detecting similarities and dissimilarities across items is vital in order to determine category‐relevant features. Previous research found evidence that infants acquire a single category more easily with paired presentations in comparison with single presentations (Oakes & Ribar, 2005, Infancy, 7, 85; Oakes & Kovack‐Lesh, 2007, Cogniție, Creier, Comportament / Cognition, Brain, Behavior, XI, 661). Here, we focus on infants' acquisition of a category contrast, that is, when they are exposed to two categories. In an eye‐tracking study, we examined 10‐month‐old infants' ability to learn two novel visual categories when presented with one item at a time and with items in pairs. Infants were familiarized with pairs of items from the same category or with pairs of items from different categories (cross‐category pairs). Using a linear model with a priori contrasts, we show that infants' learning is directly related to the opportunity for category comparison: There is no evidence of category learning in the single‐item condition, improved performance when familiarized with same‐category pairs, and finally robust category learning when familiarized with cross‐category pairs. We conclude that comparison which involves items from different categories promotes category formation, by highlighting differences and promoting a discovery of category boundaries.